Informal Sector and International Capital Movement: New Evidence from Some Petroleum Countries - Zeddam Ahmed Amine (Sciendo, 2021)
The main aim of this paper is to investigate the effect of the informal economy (IE) on foreign direct investment (FDI) in a sample of petroleum producing countries (Algeria, Norway, the Russian Federation, Saudi Arabia and United States) based on data covering the period of 1991–2018 and using the Non-linear Autoregressive Distribution Lag (NARDL) model. The NARDL model was built separately for each country in the study sample. The main finding of this study is the impact of IE size on FDI inflows in all of the countries in the study sample, even if they are all producing and exporting countries. The empirical results lead to distinguish between two sub-groups. The first sub-group consists of countries whose FDI inflows have been positively affected by positive and negative shocks in the IE. These countries are characterised by a high share of natural resources in their GDP. The second sub-group consists of countries whose inward FDI has been positively affected by negative shocks in the IE and negatively affected by the positive ones. The most common feature of this subgroup is the relative independence of economics from natural resources.